Child uptake of smoking by area across the UK. Issue 9 (4th December 2013) - Hopkinson, Nicholas S; Lester-George, Adam; Ormiston-Smith, Nick; Cox, Alison; Arnott, Deborah
Abstract : Smoking is a major public health problem. As smokers age and die prematurely, the tobacco industry must continue to recruit new, young smokers. Survey data indicate that currently in the UK around 207 000 children aged 11–15 start smoking every year. We used local data on adult smoking rates to apportion national data on child smoking uptake to specific areas. The presentation of data for individual local authorities, which now have responsibility for public health, can be used to focus attention locally. For example, this analysis demonstrates that each day, 67 children, more than two classrooms full, start smoking in London.